TCPs, WUSs, and WINDs: families of transcription factors that regulate shoot meristem formation, stem cell maintenance, and somatic cell differentiation - Ikeda, Miho; Ohme-Takagi, Masaru (Frontiers in Plant Science, 2014)
In contrast to somatic mammalian cells, which cannot alter their fate, plant cells can dedifferentiate to form totipotent callus cells and regenerate a whole plant, following treatment with specific phytohormones. However, the regulatory mechanisms and key factors that control differentiation-dedifferentiation and cell totipotency have not been completely clarified in plants. Recently, several plant transcription factors that regulate meristem formation and dedifferentiation have been identified and include members of the TEOSINTE BRANCHED1/CYCLOIDEA/PROLIFERATING CELL FACTOR (TCP), WUSCHEL (WUS), and WOUND INDUCED DEDIFFERENTIATION (WIND1) families. WUS and WIND positively control plant cell totipotency, while TCP negatively controls it. Interestingly, TCP is a transcriptional activator that acts as a negative regulator of shoot meristem formation, and WUS is a transcriptional repressor that positively maintains totipotency of the stem cells of the shoot meristem. We describe here the functions of TCP, WUS, and WIND transcription factors in the regulation of differentiation-dedifferentiation by positive and negative transcriptional regulators.